Short Communication: Diversity of plant species growing during fallow period of shifting cultivation and potential of its biomass for sustainable energy production in Mahakam Ulu, East Kalimantan, Indonesia - YULIANSYAH; MUHAMMAD TAUFIQ HAQIQI; ELIS SEPTIA; DEWI MUJIASIH; HELMI ALFATH SEPTIANA; KRISNA ADIB SETIAWAN; BUDHI SETIYONO; EDDY MANGOPO ANGI; SAPARWADI; NUR MAULIDA SARI; IRAWAN WIJAYA KUSUMA; RUJEHAN; WIWIN SUWINARTI; RUDIANTO AMIRTA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Yuliansyah, Haqiqi MT, Septia E, Mujiasih D, Septiana HA, Setiawan KA, Setiyono B, Angi EM, Saparwadi, Sari NM, Kusuma IW, Rujehan, Suwinarti W, Amirta R. 2019. Short Communication: Diversity of plant species growing during fallow period of shifting cultivation and potential of its biomass for sustainable energy production in Mahakam Ulu, East Kalimantan, Indonesia. Biodiversitas 20: 2236-2242. Fallow period is a time gap, as long as 15 years, for improving natural soil fertility of land used for traditional shifting cultivation, in the tropical areas commonly used by Dayak People in Borneo Island. During this period, many biomass plant species naturally grow and develop a new forest vegetation community with shrub and medium trees, dominated by fast-growing pioneer species. In this study, we investigated the plant diversity in fallowed shifting cultivation area in Batu Majang Village, Mahakam Ulu District, East Kalimantan Province, followed by analysis of the suitability of wood characteristics for energy production. We classified the study area according to the age of fallow period as: 1-3 years, 4-6 years, 7-9 years and 10-15 years. We found 29 species among which 13 were identified as the top species according to the highest value for important value index. Potential wood biomass production increased from 3.01 m3 ha-1 to 399.62 m3 ha-1. V. pinnata and M. pearsonii showed the highest dominance which is present in almost all area based on age classification groups. Wood from V. pinnata achieved the highest calorific valueof18.00 MJ kg-1 whereas N. cadamba and M. sericea were in the second and third places with the value of 17.30 MJ kg-1 and 17.28 MJ kg-1, respectively. Therefore, V. pinnata was an important species among all other species observed because of high adaptability and high energy content. In addition, possible energy production at the end of the fallow period of 15 years was 2.92 GJ ha-1.